Strengthening Malaria Migration Surveillance at Village Level in Tanah Bumbu Regency, South Borneo, Indonesia - Nita Rahayu; Yuniarti Suryatinah; Ayunina Rizky Ferdina (Postgraduate, University of Mataram, 2023)
Tanah Bumbu Regency had implemented malaria migration surveillance in illegal mining areas. This study aimed to describe the implementation of malaria migration surveillance. The study conducted in five villages with high case incidence (HCI) i.e., Gunung Raya, Temunih, Mangkal Api, Guntung, and Teluk Kepayang, from March to October 2018. The study used an observational design with a cross-sectional approach, descriptive analysis for quantitative data, and thematic content for qualitative data. The research activity included a mass blood survey, malaria vector species, environmental survey, focus group discussion with mining workers, and in-depth interviews about the implementation of malaria migration surveillance. Socialization of malaria migration surveillance in 5 HCI villages has been carried out to the wider community. The slide positivity rate of malaria was 1.45% of 1996 participants and positive cases of malaria were detected in 75 subjects. Anopheles sp and potential larvae in swamps, rivers, ponds, and wells. Mine workers consider malaria as an occupational risk of working in forests. The workers are unwilling to get checked for blood examination or to report to the local Primary Health Centers (Puskesmas) before and after traveling to endemic areas. Cross-sectoral collaboration is carried out by community empowerment through village malaria posts